2021
DOI: 10.3390/polym13193297
|View full text |Cite
|
Sign up to set email alerts
|

Novel Analysis Methodology of Cavity Pressure Profiles in Injection-Molding Processes Using Interpretation of Machine Learning Model

Abstract: The cavity pressure profile representing the effective molding condition in a cavity is closely related to part quality. Analysis of the effect of the cavity pressure profile on quality requires prior knowledge and understanding of the injection-molding process and polymer materials. In this work, an analysis methodology to examine the effect of the cavity pressure profile on part quality is proposed. The methodology uses the interpretation of a neural network as a metamodel representing the relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 46 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…In Equation (12), means the estimate of effect size, corresponds to the -statistic, and is the total number of classifications. If epsilon squared is 1, it means perfect correlation, and if it is 0, it indicates no relationship [ 28 ]. The analysis showed that there is a significant difference between the classifications.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In Equation (12), means the estimate of effect size, corresponds to the -statistic, and is the total number of classifications. If epsilon squared is 1, it means perfect correlation, and if it is 0, it indicates no relationship [ 28 ]. The analysis showed that there is a significant difference between the classifications.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors confirmed that cavity pressure is a valuable data source that can represent the quality of injection molded products [ 27 , 28 , 29 ]. In a typical cavity pressure profile, several feature points can be extracted that define the characteristics of the injection molding conditions [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, most of the existing design models for slab-column connections lack a physical sense, which is due to their being empirical or semi-empirical [4]. On the other hand, machine learning (ML) models can model the behavior with a high level of precision and consistency [8][9][10].…”
Section: Introductionmentioning
confidence: 99%